Small bowel obstruction caused by vas deferens: a first documented report. (6th June 2018) - Davies, J; Parmar, J; Finlay, I; Day, J
Abstract : Small bowel obstruction (SBO) is one of the most common causes for an acute surgical admission. Most of the time SBO is a result of common causes such as postoperative adhesions. However, rare and unusual causes of SBO do exist which can be challenging for surgeons. We report a first documented case of SBO caused by a remnant of the vas deferens in a 24-year-old patient with a history of gastroschisis and left orchidectomy. Clinical presentation, investigations, imaging and management of this case are described. To summarise, clinicians should keep an open mind in dealing with patients with intestinal obstruction due to the rare and atypical causes.